Mathematical values inculcation: a perspective of Islamic world views - Liman, Mukhtar Alhaji; Ibrahim, Mohd Burhan; Salleh, Mohamad Johdi (2013)
The emergence of the need of education of best quality by many world nations brought the idea of values inculcation in the attainment of this noble objective. Therefore, this paper examined Islamic universal mathematical values inculcation model in mathematics teaching and learning. Comparison between Islamic universal values and the values in the context of mathematics contents delivery were examined. The study employ mixed methodological techniques for its data analyses which include: Structural equation modeling (SEM) and qualitative approach. A purposeful sampling technique of n=509 mathematics teachers respondents were used for the study. The authors also argue that for effective mathematical contents delivery should be one that advocates values inculcation. Suggestions were made on effective Islamic universal values inculcations in mathematics teaching and learning in encounter.